The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.physrep.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Brownian motion

Abstract: a b s t r a c tOver the past one hundred years, Brownian motion theory has contributed substantially to our understanding of various microscopic phenomena. Originally proposed as a phenomenological paradigm for atomistic matter interactions, the theory has since evolved into a broad and vivid research area, with an ever increasing number of applications in biology, chemistry, finance, and physics. The mathematical description of stochastic processes has led to new approaches in other fields, culminating in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
280
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(306 citation statements)
references
References 507 publications
(1,653 reference statements)
3
280
0
10
Order By: Relevance
“…Despite a high motivation toward the construction of a unifying approach, there is currently no consensus on the form of Langevin and master equations describing a relativistic Brownian particle. Several versions were proposed in recent years [1], but their status and validity range are often obscure. The difficulties are many, and some are fundamental to relativistic many-body dynamics [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a high motivation toward the construction of a unifying approach, there is currently no consensus on the form of Langevin and master equations describing a relativistic Brownian particle. Several versions were proposed in recent years [1], but their status and validity range are often obscure. The difficulties are many, and some are fundamental to relativistic many-body dynamics [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Several versions were proposed in recent years [1], but their status and validity range are often obscure. The difficulties are many, and some are fundamental to relativistic many-body dynamics [1,2]. In the nonrelativistic theory, the standard equations of Brownian motion can be derived microscopically, eliminating (fast) degrees of freedom of the thermal bath with a projection operator or some other technique [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, are the evolution of dynamical systems towards equilibrium and more specifically their equilibrium probability distribution function (PDF). As reported recently [17,18,23], the description of the motion of relativistic particles with respect to the observer's time, t, and the particle's proper time, τ are completely different. To elucidate, consider the t-averaged PDF of a Brownian particle in terms of the observer's time…”
mentioning
confidence: 95%
“…To resolve the uncertainty, semi-relativistic [13] and fully relativistic [14,15] molecular dynamics simulations as well as Monte Carlo studies [16] have been performed by different groups in recent years that unequivocally favored Jüttner distribution. However, some recent investigations on relativistic Brownian motions [17,18] have revealed that stationary distributions can differ depending on the underlying time-parameterizations, a problem which never arises in Newtonian physics due to the existence of a universal time for all inertial observers. On the other hand, the maximum relative entropy principle (MREP) [19,20,21] depicts how symmetry considerations lead to different stationary distributions, each with its own merits [22].…”
mentioning
confidence: 99%
“…More formal mathematical generalization of classical Brownian motion to its relativistic counterpart is performed by Dunkel and Hänggi [6]. However, this equation describes propagation of CRs through a system of mutually independent scatterers, whereas real points of scattering are bounded by magnetic field lines along which the particles fly.…”
Section: Pos(icrc2015)463mentioning
confidence: 99%